Epidemiological study of the correlation between sociodemographic factors and adherence to vaccination against COVID-19 in the South macroregion of Minas Gerais (Research, Society and Development, 2024)
The COVID-19 pandemic brought major impacts to public health. The present study aims to analyze the sociodemographic profile of the population adherent to vaccination against COVID-19 in the South macroregion, Minas Gerais, and characterize the factors that influenced the adherence. Thus, the data made available by IBGE Cidades and Boletim Epidemiológico Coronavírus from the State Department of Health of Minas Gerais were used. Then, principal component analysis followed by multiple linear regression was performed to evaluate the effects of social, economic, and health variables on the spatial behavior of vaccination coverage, considering the frist dose (d1), second dose, and sigle dose (d2_du). This analysis identified the variables that had a direct and inverse proportional influence on vaccination adherence. It was observed that the number of elementary and secondary education institutions (var_escolar) and GDP per capita have a positive correlation with d1, while the average monthly salary of formal workes shows a negative correlation. The spatial behavior of d2_du is positively explained by d1 and var_escolar. Finally, it was concluded that sociodemographic factors had a significant impact on the vaccination adherence of the population studied against COVID-19.